ВПЛИВ СУЧАСНИХ ТРАНСФОРМАЦІЙНИХ ПРОЦЕСІВ НА ПРАВОВУ СВІДОМІСТЬ НАСЕЛЕННЯ - Пампура, Максим Валерійович (SUPREMANCE OF LAW, 2016)
The essence and content of the notion «legal consciousness» are considered. The interrelation of the contemporary transformational process and development of legal consciousness in post-totalitarian societies is analyzed. The content and main features of legal consciousness in the conditions of globalization, democratization and modernization processes in Ukraine are determined.